PERANG BAHASA ANTARA INDONESIA DAN MALAYSIA DI DUNIA MAYA - Junaidi Junaidi (University of Muhammadiyah Purwokerto, 2009)
Eventhough Indonesia and Malaysia are included in a group of Malay tribe, both countries are often faced with conflicts such as border, Indonesian workers in Malaysia, and cultural heritage claims. The conflicts between Indonesia and Malaysia can be found in the blog written by Indonesian and Malaysian bloggers. This paper aims to analyze the use of language and its meaning in the blogs”. The analysis by using discourse analysis shows that the war of language happen between Indonesian and Malaysian to respond the conflicts. The both sides have used a rough language to ridicule and to underestimate each other. The kinds of language used in the blogs are refusal, ridiculous, comparative, and metaphor. The findings of the research conclude that the blogs have been used freely to convey the feeling of hatred and battle by Indonesian and Malaysian bloggers.